2014
DOI: 10.1126/science.343.6168.290
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Plant Receptor for Extracellular ATP

Abstract: Extracellular adenosine 5'-triphosphate (ATP) is an essential signaling molecule that is perceived in mammals by plasma membrane P2-type purinoceptors. Similar ATP receptors do not exist in plants, although extracellular ATP has been shown to play critical roles in plant growth, development, and stress responses. Here, we identify an ATP-insensitive Arabidopsis mutant, dorn1 (Does not Respond to Nucleotides 1), defective in lectin receptor kinase I.9 (Arabidopsis Information Resource accession code At5g60300).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
550
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 466 publications
(568 citation statements)
references
References 39 publications
13
550
0
5
Order By: Relevance
“…Alternatively, unknown nucleotide receptors may exist. The unexpected discovery of novel ATP receptors in plants, which do not bear sequence similarity to traditional P2 receptors (Choi et al, 2014), underlines this possibility. Our ongoing efforts are directed toward identifying the molecular specifics of NTP release and sensing in our model.…”
Section: Discussionmentioning
confidence: 98%
“…Alternatively, unknown nucleotide receptors may exist. The unexpected discovery of novel ATP receptors in plants, which do not bear sequence similarity to traditional P2 receptors (Choi et al, 2014), underlines this possibility. Our ongoing efforts are directed toward identifying the molecular specifics of NTP release and sensing in our model.…”
Section: Discussionmentioning
confidence: 98%
“…On a longer time scale, Ca 2+ oscillations have been observed within individual cells (14). Thus, rapid hyperosmotic-induced Ca 2+ responses represent the initial cytosolic Ca 2+ rise preceding these secondary Ca 2+ signaling events that occur throughout the plant.Given the short time interval between stimulus and response, quantitative interrogation of the rapid hyperosmotic-induced Ca 2+ response in plants was used as a method to identify a potential osmo-sensory component (15) as well as sensory components for other stimuli such as ATP and rapid alkalization factor (RALF) peptides (16,17). One mutant line, reduced hyperosmolalityinduced [Ca 2+ ] i increase 1 (osca1), was mapped to mutations in a membrane protein At4g04340 (15).…”
mentioning
confidence: 99%
“…Given the short time interval between stimulus and response, quantitative interrogation of the rapid hyperosmotic-induced Ca 2+ response in plants was used as a method to identify a potential osmo-sensory component (15) as well as sensory components for other stimuli such as ATP and rapid alkalization factor (RALF) peptides (16,17). One mutant line, reduced hyperosmolalityinduced [Ca 2+ ] i increase 1 (osca1), was mapped to mutations in a membrane protein At4g04340 (15).…”
mentioning
confidence: 99%
“…Similar to animal cells, plant cells can also release ATP from the cytosol (via ABC transporters or exocytosis) and hydrolyse eATP (by apoplastic nucleotidases or apyrases) (Thomas et al 2000;Kim et al 2006;Riewe et al 2008;Tanaka et al 2010aTanaka et al , 2014Cao et al 2014;Choi et al 2014;Sheppard 2014). However, no study has shown the existence doi: 10.17221/128/2015-PPS of ATP synthase in the plant cell surface or plasma membrane, indicating that intracellular ATP (iATP) could be the major, even sole, resource of plant eATP.…”
mentioning
confidence: 99%
“…Some studies have revealed that artificially changing the levels of plant eATP can influence the growth, development, and survival of plant cells (Tanaka et al 2010aCao et al 2014;Choi et al 2014;Sheppard 2014). And, eATP appears to regulate some unique physiological processes of plants, such as thigmotropism and gravitropism of roots (Tanaka et al 2010aand references cited therein).…”
mentioning
confidence: 99%